Faktor-Faktor Psikologis Terhadap Adversity Quotient Mahasiswa Penghafal Al-Qur’an - Theofani, Atina Mahdiyya; Suryadi, Bambang (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2019)
This study aims to determine the effect of emotional intelligence, achievement motivation, and demographic profile on the adversity quotient of students memorizing Qur'an. This study involved a sample of 205 students memorizing the Qur'an with a nonprobability sampling technique (purposive sampling). Measuring instruments used in this study are adaptations of Adversity Quotient Profile (AQP), Assessing Emotion Scale (AES), Achievement Motivation Inventory (AMI). Test the validity of measuring instruments using the technique of confimatory factor analysis (CFA). Data analysis uses multiple regression analysis techniques. The results showed a significant influence on emotional intelligence, achievement motivation, and demographic profile on the adversity quotient of students memorizing the Qur'an. The significant dimensions that influence are the regulation of emotional self from emotional intelligence variables and self-control of achievement motivation variables. Future studies are expected to develop this research by involving variables of religiosity, spirituality, and parenting parents.